Variasi Penggunaan Strategi Kesantunan sebagai Penanda Subordinasi Mahasiswa dalam Interaksi Lisan Tertulis - Dian Budiarti (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
Studies on politeness strategies have been carried out in various fields. However, the study in the context of oral and written interactions is still limited. The purpose of this study is to present the use of students' language politeness strategies in oral and written interactions and to reveal the causes of differences in their choice of use. The primary data in this study were 50 instant message texts between students and lecturers. Data were analyzed using the categorization of politeness strategies from Brown & Levinson (1987), which was supported by data from interviews with 7 participants. This study found that 4 out of 5 categories of politeness strategies were used by students, which were dominated by negative politeness strategies. It indicates an awareness of the asymmetric power relationship between the two, which makes them feel the need to be careful so that what is conveyed does not threaten their faces. In addition, it was found that the reasons behind the variation in the use of politeness strategies were related to educational ritualism, looseness of domination of power, the intensity of interaction, and the purpose of sending messages.